Big Bang-Big Crunch Algorithm for Dynamic Deployment of Wireless Sensor Network - R S Uppal; Shakti Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper proposes soft computing technique Big Bang-Big Crunch (BB-BC) to address the main issue of deployment of wireless sensor networks. Deployment is the main factor that significantly affects the performance of the wireless sensor network. This approach maximizes the coverage area of the given set of sensors. We implemented our approach in MATLAB and compared it with ABC approach and found that the proposed approach is much better than the said approach.